Analyzing the Prosocial and Antisocial Behaviors of Varsity Team Athletes - Sema GEREK; Hikmet TÜRKAY (ümit doğan üstün, 2023)
This study's primary objective is to identify behavioural differences among varsity team athletes through an analysis of their prosocial and antisocial conduct in relation to a variety of variables. A scanning model, which is classified as a quantitative research method, was utilised in the study. The research study group comprises students enrolled at Osmaniye Korkut Ata University who are actively engaged in team sports during the academic year 2022-2023. The Prosocial and Antisocial Behaviour Scale in Sports, which was adapted from Turkish by Balcıkanlı (2013) and developed by Kavussanu and Boardley (2009), was utilised to assess the conduct of team athlete students. Kolmogorov-Smirnov (n>50) and Skewness-Kurtosis tests were utilised in the analysis of the research data to determine whether or not the measurements followed a normal distribution; since the measurements did follow a normal distribution, parametric tests were applied. According to the research findings, there are significant differences in prosocial and antisocial behaviour among university students who participate in team sports. These variations are contingent upon factors such as age, gender, academic discipline apart from sports sciences, and the number of siblings. By proposing that university students demonstrate greater prosocial behaviour in team sports, it is anticipated that these results will make a scholarly contribution to the current body of knowledge.